Perspectives on Elderly Crime and Victimization - Kratcoski, Peter C.; Edelbacher, Maximilian (Springer, 2018)
The populations of nations throughout the world, especially those economically developed countries of North America, Europe, and Asia, have become older. In the United States and Europe, the “baby boomer” generation born soon after World War II ended is now approaching “senior citizen” status. Later generations of child-bearers in various countries, either by choice or by adherence to government policies, had fewer children than families in the past generations. At the present time, many countries are seeing a population decline and a change in the structure of the population, with a larger segment of the population in the older age category. This change has not gone unnoticed by the “shakers and doers” in the industry, retail marketing, and the housing market, as well as political leaders. For example, in the past, housing, clothing styles, and recreational and leisure time operations were geared toward the younger and middle-aged populations. Now, there has been a dramatic shift in focus toward older persons who have the time, funds, and resources for housing, clothing, and activities consistent with an older age lifestyle. There has also been a gradual trend in the interests of criminologists to study the causes of elderly crime and elderly victimization by crime, as well as criminal justice practitioners who respond to elderly crime and elderly victims of crime. The chapters in this book were written by criminologists who have completed research on the causes of elderly crime and the response of the justice system to those older offenders convicted of a criminal act and criminal justice practitioners who have dealt with many criminal cases involving the elderly during their careers. The authors of the chapters focus on the criminal behavior of the elderly and provide valuable information on the causes of elderly crime, the scope of the problem, and the ways the criminal justice systems of their countries respond to older offenders.